Sistem Pakar Diagnosis Penyakit Gigi dengan Metode Breadth First Search berbasis Instant Messaging LINE Messenger - Darmaastawan, Kadek; Lanang Bagus Suputra Jaya Amertha, Putu; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2021)
Toothache is a disease commonly experienced by humans, therefore must be treated immediately to prevent serious impact. One of the initial treatments is to consult a dental expert. Current technological developments have been able to transform an expert's knowledge into a digital form called an expert system for easy and fast access. Currently, most expert systems are based on the web and Android/iOS platforms. The development of an expert system based on web applications or Android/iOS faces several challenges. The challenge is that it requires a lot of development time and costs because it has to develop an interface and requires a server with good performance. The challenge faced from the user's side is that more storage space is needed to install an expert system on smartphones. The solution proposed in this study is to develop an expert dental disease diagnosis system using the Breadth First Search Method based on instant messaging. One of the most popular instant messaging in Indonesia is LINE Messenger. This research succeeded in developing a dental disease diagnosis expert system based on LINE Messenger that is easily accessible and capable of diagnosing diseases with an accuracy rate of 90.9%.